2003
DOI: 10.1103/physrevb.67.052405
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of magnetic polaronic states inLa0.70Sr0.30Mn1

Abstract: We have performed x-ray, electrical resistivity, and Raman scattering measurements in La 0.70 Sr 0.30 Mn 1Ϫx Fe x O 3 manganites, with x varying from 0 to 0.40. The appearance of new peaks in the Raman spectra as the Fe content increases is attributed to either otherwise forbidden Raman modes that become active due to symmetry breaking effect or to the phonon density of states features, which arise due to a disorderinduced phenomenon. The softening of some phonon modes suggests the evidence of magnetic polaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Souza Filho et al [18] have reported the presence of magnetic polaronic state in Fe doped LSMO system as a consequence of shift in XRD peaks towards lower angles. Very similar behavior are found in XRD pattern for our samples also, we will check out the possible reasons of the increase in lattice volume with Fe doping in connection with electrical and magnetic properties.…”
Section: Resultsmentioning
confidence: 98%
“…Souza Filho et al [18] have reported the presence of magnetic polaronic state in Fe doped LSMO system as a consequence of shift in XRD peaks towards lower angles. Very similar behavior are found in XRD pattern for our samples also, we will check out the possible reasons of the increase in lattice volume with Fe doping in connection with electrical and magnetic properties.…”
Section: Resultsmentioning
confidence: 98%
“…A comparison shows that the peak 1 at ¾465 cm 1 may be due to Fe doping, while the intense peak at ¾518 cm 1 , seen in both the samples but not reported either for the single crystal or in bulk polycrystalline samples, may represent the nano-character of the sample. Souza Filho et al 8 studying rhombohedral La 0.70 Sr 0.30 MnO 3 also observed a broad mode at 524 cm 1 for Fe content ½0.20 and assigned the mode as a density-of-states feature activated by loss of local symmetry in the oxygen sublattice. The enhancement in the intensity of Raman peaks was suggested to be due to the decrease in the average particle size.…”
Section: Ambient Studies Using Raman Spectroscopymentioning
confidence: 99%
“…Also, the mode at 524 cm 1 has been assigned to the oxygen sublattice with reduced symmetry. 8 Raman spectra are sensitive to local symmetry reduction since the undistorted cubic perovskite does not exhibit firstorder peaks at all. In oxidized Sr Fe x Ti 1 x O 3 samples, strong indications of a Jahn-Teller distortion around Fe 4C ions is seen through the peaks at 475 and 690 cm 1 , which decrease with increasing iron concentration.…”
Section: Ambient Studies Using Raman Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations